2013
DOI: 10.1097/aud.0b013e318294e3d2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stimulus Rise-Time on the Ocular Vestibular-Evoked Myogenic Potential to Bone-Conducted Vibration

Abstract: In summary, in this sample of healthy subjects, the most effective stimulus for eliciting oVEMP n10 to BCV at Fz was found to be a tone burst with a rise-time of 0 msec at low stimulus frequency (250 or 500 Hz).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 5 publications
2
25
0
Order By: Relevance
“…The otolith organs may be sensitive to changes in acceleration over time (Curthoys et al, 2006, Jones et al, 2011) and thus VEMPs are larger and peak earlier if the onset of a stimulus (i.e. rise time) is short (Cheng and Murofushi, 2001b, Burgess et al, 2013). In fact, stimulus rise time is one of the major factors determining reflex latency and for this reason it is important to collect normal data for each stimulus.…”
Section: Optimal Stimulus Parameters: Air-conducted (Ac) Soundmentioning
confidence: 99%
“…The otolith organs may be sensitive to changes in acceleration over time (Curthoys et al, 2006, Jones et al, 2011) and thus VEMPs are larger and peak earlier if the onset of a stimulus (i.e. rise time) is short (Cheng and Murofushi, 2001b, Burgess et al, 2013). In fact, stimulus rise time is one of the major factors determining reflex latency and for this reason it is important to collect normal data for each stimulus.…”
Section: Optimal Stimulus Parameters: Air-conducted (Ac) Soundmentioning
confidence: 99%
“…To the Editor: Burgess et al (2013) have reported new data on the effects of rise time and stimulus frequency on the ocular vestibular evoked myogenic potential (OVEMP) evoked by skull vibration. In contrast to previous reports, they found a broad tuning curve with no clear best frequency.…”
mentioning
confidence: 99%
“…Neither was the amplitude of the induced acceleration measured for different frequencies (cf. The methodological approach of Burgess et al (2013) means the tuning properties of the OVEMP they showed with vibration are likely to be confounded by the idiosyncrasies of both their stimulus manipulations and their subjects' tolerance of different stimulus intensities. The use of individual subjective comfort criteria would certainly produce a nonconstant peak acceleration profile across frequency.…”
mentioning
confidence: 99%
See 2 more Smart Citations